The APPLICATION OF THE PERT METHOD IN THE AUDIT OF BUSINESS OF AGRICULTURAL ENTERPRISES - Milojević, Ivan; Krstić, Dalibor; Jovičić, Aleksandar (Economics of Agriculture, 2022)
The audit of agribusiness operations is present in companies with significant agricultural potential, which can be accepted as justified in our conditions. The agricultural sector is one of the development sectors in the Republic of Serbia, which necessarily represents a significant economic resource, and therefore the object of business audit. The factors of modern audit-based processes are conditioned by the complexity and subject specificities of the object being audited, which is expressed in the conditions of the agricultural sector. This paper will present the application of a quantitative planning method that is widely used in complex processes, and which can also be applied in the auditing processes of agricultural enterprises.